The Origin of Esotericism: An Analysis of the Ismaili Esoteric Approach to Qur’anic Interpretation - Mahmoud, Ramy (Jurnal Studi Ilmu-ilmu Al-Qur'an dan Hadis, 2024)
This study examines the Ismaili method of interpreting Qur’anic verses, focusing on their esoteric hermeneutics. The Quran serves as a fundamental legislative source for various theological factions, each seeking to substantiate their claims by referencing its verses. It also stands as a principal source for muhaddithin, fuqahā (jurisprudents), and others, contributing to the emergence of tafsir, a discipline aimed at elucidating the Quran's meanings and intentions. Consequently, different schools of interpretation, or tafsir, have developed over time. One strand of interpretation adheres to the literal meaning of the text, known as Zāhir, while another explores mystical or esoteric meanings, termed Bātin, occasionally without strong support from Arabic language or Qur’anic and Hadith evidence. Among Shiite sects, the Ismailis distinguish themselves as one of the most enduring, recognizing Ismail bin Ja'far al-Sādiq as their Imam and establishing influential states in Islamic history, such as the Qarmatian state in Bahrain (899–1077) and the Fatimid Caliphate in North Africa (909/1171). To thoroughly investigate this subject, a qualitative research approach is proposed. Given the historical and theological nature of the topic, qualitative methods, such as textual analysis and historical research, facilitate a comprehensive exploration and interpretation of complex phenomena. The findings of this research indicate that Ismailism has heavily relied on the esoteric interpretation of Qur’anic verses since its inception, aligning with Ismaili belief systems, with Qur’anic verses assuming a more significant role than Hadith in their doctrinal framework. The essence of this article lies in delving into the Ismaili approach to esoteric hermeneutics, predominantly drawing from the sect's primary sources.